Antibacterial activity of crude ethanolic and fractionated extracts of Punica granatum Linn. fruit peels - Éverton Silva Santos; Jaqueline Hoscheid; Patricia Terron Ghezzi da Mata (São Paulo State University (UNESP), 2015)
Currently it is clear the need to develop new antimicrobial seeking to solve problems such as antibiotic resistance, in this context medicinal plants has been using a prominent place, and knowledge of popular medicine shows itself to be a promising search tool. Peel of Punica granatum fruits are popularly used for the treatment of diarrhea, eye and upper airway inflammation, and in the external treatment of infectious sores. Thus, this study had the objective to evaluate the in vitro inhibitory effect of the crude ethanol extract of peels of P. granatum, three organic fractions and also fractions obtained by column chromatography, on reference microorganisms (Staphylococcus aureus, Escherichia coli, Salmonella typhimurium and Pseudomonas aeruginosa) by disk diffusion method. The obtained results evidenced that the ethyl acetate and aqueous fractions facing S. aureus and E. coli showed significant antimicrobial activity, close to the antimicrobial gentamicin and penicillin, respectively. In its turn the crude ethanolic extract of P. granatum and aqueous fraction showed inhibitory effect similar to the antimicrobial tetracycline facing P. aeruginosa. It was observed an increase in the inhibition of the microorganisms with increasing extract volume (from 10 to 30 µL), being S. aureus and P. aeruginosa the most susceptible microorganisms. Differences in activity between the extracts and fractions can be partly explained by qualitative and quantitative variations in the secondary metabolites present in the extracts and fractions.